Pengaruh BOPO dan CAR terhadap Pembiayaan Mudharabah pada Bank Umum Syariah di Indonesia Periode 2015-2020 - Mika Septia Rezadi; Eka Sri Wahyuni; Rizky Hariyadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of BOPO and CAR on mudharabah financing in Islamic commercial banks in Indonesia. This type of research uses quantitative research methods and this research uses secondary data from the annual financial reports of Islamic commercial banks for the 2015-2020 period. The population in this study are Islamic commercial banks in Indonesia. The sample of this research is the bank's annual financial statements using purposive sampling method, and there are 7 sharia commercial banks that meet the criteria. Data analysis methods in this study used descriptive analysis, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), and multiple linear regression tests. To test the hypothesis using a simultaneous test (F test), partial test (T test), coefficient of determination test. The results of the study stated that the BOPO variable had a positive effect on mudharabah financing, as well as the CAR variable had a positive effect on mudharabah financing. And the BOPO and CAR variables simultaneously affect mudharabah financing at Islamic commercial banks in Indonesia for the 2015-2020 period.